Simulation model of environmental sustainability in Malaysia and Sarawak using System Dynamics / Margaret Chan Kit Yok … [et.al]. - Kit Yok, Margaret Chan; Yap, Bee Wah; Ting, Siew King; Wong, Mui Hung; Lawai, Elly (2012)
Malaysia is striving to attain the status of a fully developed nation by 2020 and currently is in the transition from labour-intensive and assemble-type production to capital and technology intensive production, and finally to the knowledge-based economy. Malaysia ranks higher among the emerging economies. During the 2004 - 2007 periods, the GDP grew from RM427 billion to RM 504 billion. The rapid industrial progress is also followed by a population increase from 18.38 million to about 26 million in 2008. The increase in population and economic growth has resulted in the increased demand for goods and services, which in turn lead to increase in waste generation and pressure on the natural resources and stresses to the environment. Currently, the Malaysian Government is adopting a holistic management of the environment and natural resources through the setting up of many agencies in the collection and compilation of data pertaining to demographic changes, industrial production, agricultural production and the supply of water and electricity.